Household food insecurity and novel complementary feeding methods in New Zealand families - Ioanna Katiforis; Claire Smith; Jillian J. Haszard; Sara E. Styles; Claudia Leong; Rachael W. Taylor; Cathryn A. Conlon; Kathryn L. Beck; Pamela R. vonHurst; Lisa A. Te Morenga; Lisa Daniels; Kimberley J. Brown; et al. (Maternal and Child Nutrition)
Abstract Optimal nutrition during infancy is critical given its influence on lifelong health and wellbeing. Two novel methods of infant complementary feeding, commercial baby food pouch use and baby‐led weaning (BLW), are becoming increasingly popular worldwide. Household food insecurity may influence complementary feeding practices adopted by families, but no studies have investigated the use of BLW and baby food pouches in families experiencing food insecurity. The First Foods New Zealand study was a multicentre, observational study in infants 7.0–9.9 months of age. Households (n = 604) were classified into one of three categories of food insecurity (severely food insecure, moderately food insecure, and food secure). The use of complementary feeding practices was assessed via a self‐administered questionnaire, both at the current age (mean 8.4 months) and retrospectively at 6 months. Mothers experiencing severe food insecurity had 5.70 times the odds of currently using commercial baby food pouches frequently (≥5 times/week) compared to food secure mothers (95% CI [1.54, 21.01]), reporting that pouches were ‘easy to use’ (89%) and made it ‘easy to get fruits and vegetables in’ (64%). In contrast, no evidence of a difference in the prevalence of current BLW was observed among mothers experiencing moderate food insecurity (adjusted OR; 1.28, 95% CI [0.73, 2.24]) or severe food insecurity (adjusted OR; 1.03, 95% CI [0.44, 2.43]) compared to food secure mothers. The high prevalence of frequent commercial baby food pouch use in food insecure households underscores the need for research to determine whether frequent pouch use impacts infant health.